Determinants of modern contraceptive use among postpartum women in two health facilities in urban Ghana: a cross-sectional study - Jonathan Ian Coomson; Abubakar Manu (BMC, 2019)
Abstract Background Postpartum contraception is important for spacing and limiting childbirth. Although the use of modern contraception has been shown to reduce maternal and child morbidities and mortalities, postpartum women have one of the highest unmet needs for family planning. Inter-birth intervals less than 24 months have adverse effects on both the mother and the child, yet very limited empirical evidence exist on contraceptive use among postpartum women in Ghana. This study sought to determine the prevalence and determinants of modern contraceptive use among postpartum women in the Tema Metropolis, Ghana. Methods A facility-based cross-sectional survey was conducted among 320 postpartum women with babies aged between three and 15 months. Participants were recruited from child welfare clinics in two government health facilities in the Tema metropolitan area using a simple random sampling technique. Data were analyzed using STATA version 15. Chi-square and multiple logistic regressions techniques were used to examine associations between postpartum contraceptive use and key independent variables. Statistical significance was set at p = 0.05. Adjusted odds ratios and their 95% confidence intervals were used to assess the strength of association. Results The prevalence rate of modern contraceptive use among postpartum women was 26.3%. Postpartum contraceptive use was significantly associated with past contraceptive use [AOR = 7.7 (95%CI: 3.4-17.5)]; return of menses [AOR = 4.3 (95%CI: 1.7-11.3)]; resumption of sexual activity [AOR = 4.7 (95%CI: 1.4-15.4)]; discussion of family planning with male partner [AOR = 3.1 (95%CI: 1.03-9.2)]; male partners' approval of modern contraception [AOR = 18.1 (95%CI: 6.3-51.6)]; family planning counselling received during antenatal care [AOR = 3.5 (95%CI: 1.3-9.9)] and knowledge of at least one modern methods of contraception available at the health facility [AOR = 4.7 (95%CI: 1.9-11.5)]. Conclusions Postpartum contraceptive uptake is low among women in the Tema area. Factors that influence modern contraceptive uptake among postpartum women include past modern contraceptive use, resumption of sexual activity and menstruation, male partner involvement in contraception, family planning counselling during antenatal care and knowledge of the modern methods of contraception available at the health facility. Strengthening family planning education and counselling during antenatal care and using a multi-prong strategy to engage men as partners in family planning will improve postpartum contraceptive uptake.